Effects of vortex tube on exhaust emissions during cold start of diesel engines - Adem Celik; Mehmet Yilmaz; Omer Faruk Yildiz (Applications in Energy and Combustion Science, 2021)
This study investigates the emissions of a 6-cylinder direct injection (DI) diesel engine with vortex tube for cold start conditions. Four ambient temperatures: 5 °C, −3 °C, 0 °C and 4C were considered. The compressed air required to operate the vortex tube was supplied from compressed air cylinders from pneumatic brake system components located in heavy vehicles. The air from the compressed air tanks entered the vortex tube and the vortex emerged from the tube as hot and cold air. The hot air from the vortex tube was mixed with the intake air in the intake manifold to make the intake air hotter. Emissions analysis was conducted for carbon monoxide (CO), hydrocarbons (HC), nitrogen oxides (NOx), and particulate matter (PM). Exhaust emission characteristics for the engine with vortex tube and without vortex tube were obtained and the results were compared with each other. The cold starting performance and fuel consumption of the diesel engine could be improved by using vortex tubes. The use of the vortex tube increased the intake air temperature, which decreased durations of engine starting–cranking, cranking–idling, and idling–stabling and reduced the fuel consumption. CO and PM emissions decreased, but HC and NOx emissions increased by using vortex tube.